1988
DOI: 10.1016/0304-3959(88)90276-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing chronic pain from spinal cord injury to chronic pain of other origins

Abstract: Acknowledged as a serious complaint of spinal cord injured (SCI) patients, chronic pain in this population is neither well studied nor well understood. To assess the quality and intensity of pain, a group of 49 SCI patients seeking treatment for chronic pain was compared to a general group of 95 patients from the Comprehensive Pain Clinic (CPC) on selected demographic variables, the McGill Pain Questionnaire (MPQ) and the Minnesota Multiphasic Personality Inventory (MMPI). The SCI patients were categorized as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 19 publications
2
16
0
1
Order By: Relevance
“…Some researchers believe that it has a minor impact, 2 whilst others argue that its impact is signi®cant. 3,4 Britell and Mariano (1991) summarised the spinal cord injury pain literature and found that the prevalence of pain ranged from 27 ± 77%, providing evidence that it is a major problem and that it should not be neglected.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers believe that it has a minor impact, 2 whilst others argue that its impact is signi®cant. 3,4 Britell and Mariano (1991) summarised the spinal cord injury pain literature and found that the prevalence of pain ranged from 27 ± 77%, providing evidence that it is a major problem and that it should not be neglected.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Pain negatively interferes with sleep, return to work, health-related quality of life and participation in social activities. 3 In addition, pain is associated with poorer rehabilitation outcomes and directly contributes to disability.…”
Section: Introductionmentioning
confidence: 99%
“…1 NP is common, with the prevalence of below-level pain after SCI reported as 34% and at-level pain reported as 42%. 2 Specifically within Canada, NP after SCI is the most common complication reported by 1549 people with SCI. 3 Despite the high frequency of pain in those with SCI and its significant impact on quality of life, management of pain remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Pain seems to have an early onset after the injury, 2 ± 4,6,10 is reported mainly from below or at the level of the lesion, 2,5,6,10 and is mostly classi®ed as neurogenic/neuropathic. 1,10,13 (The term neurogenic will be used throughout this paper). According to Ravenscroft and colleagues 4 a higher incidence of pain is seen in patients with complete injuries.…”
Section: Introductionmentioning
confidence: 99%
“…However, others have reported a higher incidence in those with incomplete lesions 6,8,10 and this has been supported by autopsy ®ndings, 14 further supported by the ®nding that patients with incomplete lesions have more severe pain than those with complete lesions. 13 Age has previously been reported to in¯uence the vulnerability to pain. 15,16 StoÈ rmer 2 found a signi®cant di erence between age at injury and the presence of pain in SCI patients.…”
Section: Introductionmentioning
confidence: 99%